Intestinal CD103+CD11b+ cDC2 Conventional Dendritic Cells Are Required for Primary CD4+ T and B Cell Responses to Soluble Flagellin - Flores-Langarica, Adriana; Cook, Charlotte; Müller Luda, Katarzyna; Persson, Emma K.; Marshall, Jennifer L.; Beristain-Covarrubias, Nonantzin; Yam-Puc, Juan Carlos; Dahlgren, Madelene; Persson, Jenny J.; Uematsu, Satoshi; Akira, Shizuo; Henderson, Ian R.; et al. (Frontiers in Immunology, 2018)
Systemic immunization with soluble flagellin (sFliC) from Salmonella Typhimurium induces mucosal responses, offering potential as an adjuvant platform for vaccines. Moreover, this engagement of mucosal immunity is necessary for optimal systemic immunity, demonstrating an interaction between these two semi-autonomous immune systems. Although TLR5 and CD103+CD11b+ cDC2 contribute to this process, the relationship between these is unclear in the early activation of T cells and the development of antigen-specific B cell responses. In this work, we use TLR5-deficient mice and CD11c-cre.Irf4fl/fl mice (which have reduced numbers of cDC2, particularly intestinal CD103+CD11b+ cDCs), to address these points by studying the responses concurrently in the spleen and the mesenteric lymph nodes (MLN). We show that CD103+CD11b+ cDC2 respond rapidly and accumulate in the MLN after immunization with sFliC in a TLR5-dependent manner. Furthermore, we identify that whilst CD103+CD11b+ cDC2 are essential for the induction of primary T and B cell responses in the mucosa, they do not play such a central role for the induction of these responses in the spleen. Additionally, we show the involvement of CD103+CD11b+ cDC2 in the induction of Th2-associated responses. Since in CD11c-cre.Irf4fl/fl mice showed a reduced primary FliC-specific IgG1 responses, but enhanced Th1-associated IgG2c responses. These data expand our current understanding of the mucosal immune responses promoted by sFliC and highlights the potential of this adjuvant for vaccine usage by taking advantage of the functionality of mucosal CD103+CD11b+ cDC2.